North of Athabasca : Slave Lake and Mackenzie River documents of the North West Company, 1800-1821 - Keith, Lloyd (Rupert's Land Record Society series., 2001)
"The fur trade was an important building block in Canada's history. While much is known about the Hudson's Bay Company, information about the North Wet Company in the Slave Lake and Mackenzie River Districts has been scattered in various archives. In North of Athabasca Lloyd Keith provides the first detailed, document-based history of this pioneering company." "Using unused or little-known documents, Keith fills in gaps and corrects inconsistencies in previous information about the company. North of Athabasca not only includes the extensively annotated texts to eleven North West Company documents but Keith's introductory essay amplifies what is known about the context of the fur trade. His biographical notes provide personal details about the proprietors and clerks involved in the fur trade as well as the engages and aboriginal trading leaders. A sketch of the trading activities of every Native mentioned in the journals is included. Engages are shown to be more than labouring drones - Keith demonstrates that men such as Jean-Baptiste LaPrise were as important in furthering the interests of the North West Company north of Athabasca as any of the clerks or proprietors who kept the accounts and wrote the journals included here. The journals, often in fractured English or colloquial Canadian French, and incorporating aboriginal terminology, make intriguing reading. A glossary is provided to assist with some of the more arcane terms." "North of Athabasca fills an important void in the literature on this period and region Readers interested in fur trade history as well as students of exploration, genealogy, ethnography, and Native studies will find this a welcome addition to the literature on a fascinating topic."--Jacket